The Maternal Death Surveillance System in Nepal: Current Status and Challenges Ahead : DOI: https://doi.org/10.46405/ejms.v6i9.532 - Sharma , Sharad Kumar (Europasian Journal of Medical Sciences, 2024)
A robust monitoring and documentation of maternal deaths are critical for understanding the extent, context, and identifying probable solutions for addressing the preventable deaths. In Nepal, the current maternal death surveillance system (including both the health facility and community-based maternal deaths) has been in operation for about a decade now. As of mid-2022, the system has been introduced in 94 hospitals and 2,123 communities (Wards). The recent data (2020-2022) on the cases of maternal deaths generated by the system show broad similarity with those based on the census-based estimates for the year 2021. Considerable differences exist in the reasons for maternal deaths between health facility and community-based data. Some of the existing major challenges in the system include, identifying causes of death correctly within a reasonable time frame, identifying realistic solutions to the timely and appropriate response actions, and ensuring that the system works effectively before scaling up to other areas within the country. These need to be addressed for the system to function as an effective tool for tracking maternal deaths and reducing preventable maternal death in Nepal.